PENINGKATAN KOMPETENSI GURU DALAM MENGINTEGRASIKAN NUMERASI PADA KEGIATAN PEMBELAJARAN - Nurwan, Nurwan; Yahya, Lailany; Badu, Syamsu Qamar (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2025)
This study focuses on enhancing the competency of primary school teachers in integrating numeracy into learning activities across subjects. Numeracy literacy is a vital 21st-century skill essential for personal and professional decision-making. The training, conducted as part of a community service program, aimed to provide teachers with practical strategies for integrating numeracy into both mathematics and non-mathematics lessons. The methods involved workshops featuring lectures, discussions, and interactive group activities, emphasizing the development of teaching materials that connect numeracy to real-world applications. Evaluation through questionnaires revealed high participant satisfaction, with 87.5% rating the training as excellent. The findings underscore the significance of teacher competence in advancing student numeracy skills and highlight the need for continued professional development in this area